Health effects of residues of ivermectin use in sheep on some organs (liver and kidney) in Karbala areas - Haneen Ismael Abdoun Kadhim; Kadhim Saleh Kahdim; Ali Redha Abid (Journal of Kerbala for Agricultural Sciences, 2024)
This study aims to detect ivermectin (IVM) residues in the liver and kidneys of sheep by using high-performance liquid chromatography (HPLC) technology. 50 samples (each of 25 livers and 25 kidneys) were collected from five different areas in Karbala Governorate. From October 2023 to January 2024. The analysis showed that samples of both liver and kidneys contaminated with ivermectin residues exceed the maximum limits for ivermectin residues, and according to the previously permitted maximum limits for ivermectin residues by the World Health Orgnasation and the Food and Agriculture Orgnasation, they show a significant difference between the regions of the governorate. As shown in the results of sheep liver and according to region (AL Hur, Al Hussaina, center, Tauweraij and Aeen tumer) and compared with the maximum limits of residues in the liver (0.06) The results were higher than the normal limit for residues (3.74, 1.87, 1.13, 0.52 and 0.21) respectively. As for the results of sheep kidneys and according to regions (Al Hussaina, center, Aeen tumer, Tauweraij and AL Hur) and compared with the maximum limits of residues in the kidney (0.02) The results were higher than the normal limit for residues (3.51, 2.44, 1.68, 0.82 and 0.37) respectively. The results showed that contamination of foods of animal origin with pesticides occurs due to incorrect use of the pesticide, failure to take into account the withdrawal period of the pesticide in the tissues of the animal’s body, and failure to observe special instructions when using it. The results of this study confirm the need for monitoring programs for eliminating pesticide residues and external parasites in animal products to protect consumer health from risks of exposure to these residues.